Idealisme Ekalawya Dalam Wiracarita Mahabharata Dan Refleksi Pendidikan Di Era Tatanan Baru - I Made Arsa Wiguna (Jurnal Penelitian Agama Hindu, 2021)
This paper aims to interpret the learning idealism of the Ekalawya figure in the Mahabharata and translate it as a reflection of the learning process in this era of the new order. The problematization between regulations and the real conditions of students has given implications for the implementation of online learning. There are many obstacles that arise, ranging from limited infrastructure, costs required and mastery of ICT, both from the teacher and student side. Refers to literary reception theory and hermeneutic methods, Ekalawya is a true disciple, his ideals such as unyielding, independence, discipline, teacher devotion, and making his yad as an obligation have led him to become a great archer. His learning experiences, such as; independent learning, obedience to the social rules of Catur Varna, respect for Drona as a teacher, and also the sincere offerings (daksina) in the form of his thumb. The limited interaction between teachers and students, hard work in doing assignments, independence and honesty of students in answering the evaluation questions, and respect that is maintained are a form of reflection on the learning experiences of Ekalawya in the era of the new order.